The Constitutional application of the Prevention of Organised Crime Act 121 of 1998 - Prinsloo, Benjamin (Department of Public Law, 2023)
Chapter 6 of the Prevention of Organised Crime Act 121 of 1998 (‘POCA') presents a means for forfeiture of property to the state which was either instrumental to an offence, or the proceeds of unlawful activity, without necessarily proving criminal wrongdoing beyond reasonable doubt. At the advent of POCA the consensus amongst legal commentators was that it could be constitutional, provided that courts remain alive to statutory and common law safeguards to prevent the unconstitutional use of POCA by the state. Over twenty years since POCA's enactment, it appears from a review of its case law that it still sits on the precipice of unconstitutionality. This thesis identifies the key constitutional issues which have arisen in the application of Chapter 6 of POCA. The premise which underlies Chapter 6 of POCA, that a criminal wrongdoer should not be allowed to benefit from their crime, cannot be faulted. What appears from the enquiry that follows is that POCA's use is wider than this premise. That is, POCA's application has gone beyond simply preventing criminals from benefitting from their crimes. In this regard, victims of crime and innocent parties are being subjected to forfeiture in terms of POCA and POCA is being used as a means of civil recovery (even where there is not criminal wrongdoing). What makes this wide use particularly problematic is the fact that POCA makes various inroads into certain Constitutional rights, as are discussed below, on the justification that these limitations of rights are in the pursuance of fighting crime. When these rights are limited for purposes other than fighting crime, the justification falls away. Given POCA's wide use in this regard, its interpretation and application in the future needs to be more narrowly interpreted and constrained, to ensure that individual rights are not unjustifiably infringed.